Conserved and species-specific oxylipin pathways in the wound-activated chemical defense of the noninvasive red alga Gracilaria chilensis and the invasive Gracilaria vermiculophylla - Rempt, Martin; Weinberger, Florian; Grosser, Katharina; Pohnert, Georg (Beilstein Journal of Organic Chemistry, 2012)
Chemical defense of the invasive red alga Gracilaria vermiculophylla has been studied and compared to that of the noninvasive but related Gracilaria chilensis. Both species rely on a wound-activated chemical defense that makes them less attractive to the herbivorous sea snail Echinolittorina peruviana. The chemical stress response of both species was monitored by LC–ESIMS-based metabolic profiling and revealed commonalities and differences. Both algae rely on a rapid lipoxygenase mediated transformation of arachidonic acid to known and novel oxylipins. Common products are 7,8-dihydroxyeicosatetraenoic acid and a novel eicosanoid with an unusual γ-lactone moiety. Several prostaglandins were predominantly formed by the invasive species. The role of some of these metabolites was investigated by surveying the attachment of E. peruviana on artificial food containing the respective oxylipins. Both algae species are defended against this general herbivore by 7,8-dihydroxyeicosatetraenoic acid, whereas the prostaglandins and the novel oxylipins were inactive at naturally occurring concentrations. The role of different oxylipins in the invasive potential of Gracilaria spp. is discussed.
Keywords: activated chemical defense; invasive species; oxylipins; prostaglandins; red algae; regulation